The resistance to methoxy polyethylene glycol-epoetin beta in anemic patients of end-stage renal disease. Issue 2 (February 2023) - Abood, Sattar J.; Abdulsahib, Waleed K.; Al-Radeef, Mohanad Y.
Abstract: Background: Chronic kidney disease (CKD) is a global disease, and the number of people affected is increasing due to driving factors such as diabetes, obesity, and hypertension, as well as increased life expectancy. Many patients with CKD suffer anemia throughout the period of their disease. Aim: This research aimed to investigate the relation between resistance to the methoxy polyethylene glycol-epoetin beta (ME-β) and angiotensin-converting enzyme (ACE) gene polymorphism. Methods: Seventy Iraqi patients with CKD on hemodialysis treatment for at least six months and receiving a subcutaneous injection of ME-β were selected to enroll in this current study. In addition to these patients, the control group of 20 healthy subjects. Baseline samples (Three blood samples) were obtained and withdrawn from each participant, then 3 and 6 months following the starting sample. In addition, a unique blood sample was taken from each participant in the control group in the early morning hours following 8 h of fasting and before dialysis (for the patients' group). Results: ACE polymorphism did not demonstrate a significant (p ˃ 0.05) relation with changing the dose of ME-β. Furthermore, there was a negative relationship between ME-β dose and hemoglobin (Hb) in CKD patients. Comparing ACE polymorphism between good and hypo-response groups shows no significant effect (p ˃ 0.05) on ME-β therapy. Moreover, the erythropoietin resistance index (ERI) was significantly (p < 0.001) lower in good responders to ME-β therapy compared to the hypo-response group. Finally, comparing the ERI of the patient, the good response group to the hypo-response group showed no significant association (p ˃ 0.05) with ACE gene polymorphism in response to ME-β therapy. Conclusion: No relation was determined between the polymorphism ACE gene and the resistance to the ME-β administration in CKD Iraqi patients.